Deficiency of GPR10 and NPFFR2 receptors leads to sex-specific prediabetic syndrome and late-onset obesity in mice - Morgan, Alena; Shekhar, Nivasini; Strnadová, Veronika; Pirník, Zdenko; Haasová, Eliška; Kopecký, Jan; Pačesová, Andrea; Železná, Blanka; Kuneš, Jaroslav; Bardová, Kristina; Maletínská, Lenka (Bioscience reports, 2024)
GPR10 and neuropeptide FF receptor 2 (NPFFR2) play important role in the regulation of food intake and energy homeostasis. Understanding the interaction between these receptors and their specific ligands, such as prolactin-releasing peptide, is essential for developing stable peptide analogs with potential for treating obesity. By breeding and characterizing double knockout (dKO) mice fed standard or high-fat diet (HFD), we provide insights into the metabolic regulation associated with the GPR10 and NPFFR2 deficiency. Both WT and dKO mice were subjected to behavioral tests and an oral glucose tolerance test. Moreover, dual-energy X-ray absorptiometry (DEXA) followed by indirect calorimetry were performed to characterize dKO mice. dKO mice of both sexes, when exposed to an HFD, showed reduced glucose tolerance, hyperinsulinemia, and insulin resistance compared with controls. Moreover, they displayed increased liver weight with worsened hepatic steatosis. Mice displayed significantly increased body weight, which was more pronounced in dKO males and caused by higher caloric intake on a standard diet, while dKO females displayed obesity characterized by increased white adipose tissue and enhanced hepatic lipid accumulation on an HFD. Moreover, dKO females exhibited anxiety-like behavior in the open field test. dKO mice on a standard diet had a lower respiratory quotient, with no significant changes in energy expenditure. These results provide insights into alterations associated with disrupted GPR10 and NPFFR2 signaling, contributing to the development of potential anti-obesity treatment.
Keywords: Animals; Female; Adipose Tissue, White; receptory neuropeptidů; ženské pohlaví; Mice, Knockout; Receptors, Neuropeptide; myši knockoutované; double KO mice; Diet, High-Fat; Obesity; energetický metabolismus; receptory spřažené s G-proteiny; impaired glucose utilization; Prediabetic State; Mice; Energy Metabolism; myši; insulin resistance; Sex Factors; obezita; Male; sexuální faktory; Insulin Resistance; inzulinová rezistence; Receptors, G-Protein-Coupled; GPR10/NPFFR2-deficient mice; mužské pohlaví; zvířata; Mice, Inbred C57BL; bílá tuková tkáň; obesity; dieta s vysokým obsahem tuků; prediabetes; myši inbrední C57BL